The Effect of Greenwashing on Firm Performance with Multiple Directorships as Moderating Variable - Eriyawan, Arista Febri; Utama, Cynthia Afriani (Pandawan, 2026)
This study investigates the impact of greenwashing on firm performance, with a focus on the moderating role of multiple directorships in the context of Indonesian public companies. Greenwashing, defined as the dissemination of misleading environmental information, has been shown to adversely affect firm performance, particularly in terms of profitability and long-term sustainability. Using data from companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, the study employs panel data analysis to examine the relationship between greenwashing, firm performance, and the influence of multiple directorships. The findings reveal that greenwashing significantly harms firm performance, as measured by Return on Assets (ROA). However, the presence of multiple directorships, while positively associated with firm performance, does not exhibit a statistically significant impact. Additionally, the moderating effect of multiple directorships on the relationship between greenwashing and firm performance is found to be negative but insignificant. These results suggest that while greenwashing poses a substantial risk to corporate financial health, the role of multiple directorships in mitigating or exacerbating this effect remains limited. The study highlights the importance of stricter Environmental, Social, and Governance (ESG) reporting standards to curb greenwashing practices and enhance corporate transparency.